2011
DOI: 10.1039/c0cs00197j
|View full text |Cite
|
Sign up to set email alerts
|

Places and chemistry: Strasbourg—a chemical crucible seen through historical personalities

Abstract: At the crossroads of Europe, having the particularity to be influenced and shaped during their history by both French and German cultures and systems, Strasbourg and Alsace have produced internationally significant science. This review is focused on the personalities of Strasbourg and Alsace who influenced many aspects of both the development and the perception of chemistry in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 636 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…The original reaction was discovered by Friedel and Crafts in the late 19th century, as the historical account has been documented in previous literature. 19,20 These reactions are often considered one of the basic organic chemistry reactions, as the reactions represent quintessential examples of electrophilic aromatic substitution covered in most of the undergraduate-level textbooks, 21 and, therefore, have been an important subject in the chemical education community. [22][23][24] Beyond their educational significance, the chemical industry has been relying on these reactions for the production of numerous carbon-based molecules for over a century.…”
Section: Jun Ohatamentioning
confidence: 99%
“…The original reaction was discovered by Friedel and Crafts in the late 19th century, as the historical account has been documented in previous literature. 19,20 These reactions are often considered one of the basic organic chemistry reactions, as the reactions represent quintessential examples of electrophilic aromatic substitution covered in most of the undergraduate-level textbooks, 21 and, therefore, have been an important subject in the chemical education community. [22][23][24] Beyond their educational significance, the chemical industry has been relying on these reactions for the production of numerous carbon-based molecules for over a century.…”
Section: Jun Ohatamentioning
confidence: 99%
“…The original reaction was discovered by Friedel and Crafts in the late 19 th century, as the historical account has been documented in previous literature. 19,20 The reactions are often considered one of the basic organic chemistry reactions, as the reactions represent quintessential examples of electrophilic-aromatic substitution covered in most of undergraduate-level textbooks, 21 and, therefore, have been an important subject in the chemical education community. [22][23][24] Beyond the educational significance, chemical industry relies on the reactions for production of numerous carbon-based molecules over a century too.…”
Section: Introductionmentioning
confidence: 99%
“…He studied the double sodium and ammonium tartrate salts and concluded that both crystals, grown from optically active and inactive tartrates, † were identical although they did not interact similarly with linearly polarized light in solution. 13 It is said that Pasteur did not believe this paradox and, being offered this racemic acid by Kestner, 14 , 15 he started the detailed analysis of the crystals. Why do two apparently identical chemicals (double sodium‐ammonium tartrate and paratartrate) have a different effect on polarized light?…”
mentioning
confidence: 99%